A Study of Blended Learning Attitude Towards Biology (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research looks at how Madhya Pradesh senior high school students' views about biology are affected by blended learning. A control group was instructed using conventional techniques, while an experimental group was exposed to blended learning tactics as part of a quasi-experimental study design. A validated Biology Attitude Questionnaire was used to gather data, and paired and independent sample t-tests were among the statistical tests used for analysis. The findings showed that both groups' views about biology had improved, with the experimental group having a little edge. The small overall impact size, however, indicates that while blended learning has promise, its efficacy relies on readiness and appropriate execution. The research emphasizes how crucial it is to include technology into teaching in order to improve learning results and cultivate positive attitudes.